1997
DOI: 10.1177/070674379704200806
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Mania in Children and Adolescents from the Indian Subcontinent

Abstract: Mania was diagnosable in Indian children and adolescents using classic DSM-III-R criteria. The clinical profile appears to be generally similar to that seen in adults. ADHD is not a comorbid condition. The presence of aggressive or disruptive behaviours and hyperactivity in childhood- and adolescent-onset mania, however, could lead to a misdiagnosis of attention-deficit hyperactivity disorder/conduct disorder (ADHD/CD). Similarly, the presence of psychotic features could lead to a misdiagnosis of schizophrenia. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
1
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
1
16
1
6
Order By: Relevance
“…We find that 6.8% of our bipolar disorder youth had a prior diagnosis of ADHD and that 2.3% of bipolar youth had been treated with a stimulant medication for ADHD. Thus, these data do not support the contention of some investigators who describe high rates (57–97%) of comorbid ADHD in early onset bipolar illness (1–7), but do support the findings of other investigators who have noted rates of ADHD which are consistent with point prevalence rates of ADHD in the general population (8–11).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…We find that 6.8% of our bipolar disorder youth had a prior diagnosis of ADHD and that 2.3% of bipolar youth had been treated with a stimulant medication for ADHD. Thus, these data do not support the contention of some investigators who describe high rates (57–97%) of comorbid ADHD in early onset bipolar illness (1–7), but do support the findings of other investigators who have noted rates of ADHD which are consistent with point prevalence rates of ADHD in the general population (8–11).…”
Section: Discussioncontrasting
confidence: 95%
“…Reports have suggested that there may be a high rate of comorbidity of attention deficit hyperactivity disorder (ADHD) and prepubertal – early onset bipolar disorder with rates of ADHD in bipolar probands ranging from 57 to 98% (1–7). Other authors have not been able to demonstrate similarly high rates of comorbid ADHD in youth with bipolar disorder (8–12). Ongoing debates and a review regarding these perspectives are found in the literature (13–15).…”
mentioning
confidence: 99%
“…4 However, our results are consistent with studies in other countries that rely on clinician diagnosis and find that the number of pediatric psychiatric hospitalizations assigned a diagnosis of BD is low relative to rates reported in the United States. Specifically, other inpatient surveys give percentage rates of total hospital admissions for PBD as a percentage of all pediatric psychiatric hospitalizations, of 1.2% to 1.7% in Denmark 9 and 2.5% 10 or 4.2% 11 in India, compared to the United States figure of 27.8%. Expressed as population-based rates, rates for PBD have been reported as 1.7 cases per 100,000 population per year in Finland 12 compared to 100.9 cases per 100,000 population per year in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…7 Similarly, population-adjusted rates of hospital discharges for children with a primary diagnosis of PBD increased linearly from 1.3 per 10,000 U.S. children in 1996 to 7.3 per 10,000 U.S. children in 2004—a 563% increase. 8 Surveys generally find lower admission rates for PBD in other countries than in the United States, with percentage estimates of total admissions for PBD ranging between 1.2% and 1.7% in Denmark 9 and between 2.5% 10 and 4.2% 11 in India. Similarly, a Finnish study found 1.7 cases of PBD per 100,000 population per year.…”
mentioning
confidence: 97%
“…Despite the evidence from these studies, doubts have been raised about the relationship between ADHD and juvenile BD (16, 19). Previous studies from this center have reported very low rates of ADHD in juvenile BD (up to 11%) raising doubts about the relationship between the two disorders (20–24). However, a major limitation of these studies was the relatively small sample sizes with the exception of one chart‐based retrospective study (23).…”
mentioning
confidence: 83%